Alfabetização visual: uma perspectiva para auto(trans)formação permanente com professores - Pereira, Andrea Garcez (2015)
This master thesis project, was developed at the Master Degree in Education, at Federal University of Santa Maria (UFSM), stems from the research Line Education, Knowledge and Professional Development. It aims to understand to what extent visual literacy is a possibility to help teachers‟ awareness in their lifelong education processes in a public school in Santa Maria - RS and it investigates how teachers externalize their seizure of knowledge relating to images meaning resources. This research is characterized as qualitative, guided by the Investigative-formative Dialogical Circles process, it aims to liberate and emancipate all teachers involved in this process, and the inspiration to this process is the Circles of Culture from Paulo Freire. This study was developed from the conception of language as a social practice, in Van Leeuwen; Kress and Halliday I found the needed theoretical basis for visual literacy, considering the different ways of communication in its context of use. Freire, Maturana and Arroyo supported the teachers lifelong education under the humanizing perspective, thinking about the path that leads us to choose our profession and how to make our practice as empowered citizens. Based on the data analysis, we can say that teachers used images in their practice intuitively, for illustration only and not as an unit of meaning, thus failing to recognize the image as an important resource in the knowledge construction. However, through the Investigative-formative Dialogical Circles there was considerable awareness about the recognition of language in its context of use, image as a language mode and, so, meaningful itself, the recognition of images meaning resources and about some implications of teacher‟s lifelong education under the humanizing perspective.